2020
DOI: 10.1371/journal.pone.0231938
|View full text |Cite
|
Sign up to set email alerts
|

Placental growth disorders and perinatal adverse outcomes in Brazilian HIV-infected pregnant women

Abstract: Fetal and placental growth disorders are common in maternal human immunodeficiency virus (HIV) infection and can be attributed to both the infection and comorbidities not associated with HIV. We describe placental growth disorders and adverse reproductive outcomes in HIV-infected pregnant women whose delivery occurred between 2001-2014 in Vitoria, Brazil. Cases with gestational age (GA) � than 22 weeks validated by ultrasonography, with placental and fetal weight dimensions at birth, were studied. Outcomes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 50 publications
0
10
0
6
Order By: Relevance
“…One study evaluated the prevalence of placental growth disorders in HIV-positive pregnant women on ART, reporting a higher prevalence of such disorders compared with international reference values, noting that restriction of placental growth was most common. 36 Another study has suggested that altered angiogenesis may be a mechanism underlying adverse outcomes in women with HIV receiving ART. 37 We noted that the timing of ART initiation did not have any influence on the occurrence of adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…One study evaluated the prevalence of placental growth disorders in HIV-positive pregnant women on ART, reporting a higher prevalence of such disorders compared with international reference values, noting that restriction of placental growth was most common. 36 Another study has suggested that altered angiogenesis may be a mechanism underlying adverse outcomes in women with HIV receiving ART. 37 We noted that the timing of ART initiation did not have any influence on the occurrence of adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the placenta has several functions, such as metabolism, nutrition, and barrier protection, in terms of embryonic development. Impairment of placental function may lead to miscarriage, preterm delivery, and stillbirth [ 149 , 150 ].…”
Section: Potential Mechanisms Of Maternal Vd Status During Pregnancy ...mentioning
confidence: 99%
“…PI effects on autophagy in placental cells may disrupt normal placental development and function. PI use during pregnancy has been variably associated with premature delivery, low birth weight, small for gestational age, maternal and neonatal endocrine dysfunction, and neonatal hematologic abnormalities [44][45][46][47][48][49] as well as abnormal placental morphology, cord insertion, and vasculature [48,[50][51][52]. ER stress underlies many toxicities associated with PI, and ER stress is important to the physiology and pathophysiology of the placenta [53].…”
Section: Lopinavir/ritonavirmentioning
confidence: 99%